Hari Ahad dalam Pandangan Islam dan Kristen - Setiawan, Hari (Lembaga Yasin AlSys, 2023)
Sunday for Christians and Sunday for Muslims have their own understanding, meaning and history for Islam and Christianity. This is what attracts the writer so that the writer wants to conduct a more in-depth study and analysis through various literature related to Sunday in the view of Islam and Christianity. Based on the background of the problem above, the writer tries to conduct a research using a scientific method. so that it is clearly known